2021
DOI: 10.28945/4839
|View full text |Cite
|
Sign up to set email alerts
|

A Four Stage Framework for the Development of a Research Problem Statement in Doctoral Dissertations

Abstract: Aim/Purpose: Provide methodology suggesting steps to doctoral mentors to work with students in constructing their research problem statement in their dissertation. Background: Writing a doctoral dissertation is a long journey, and it typically starts with writing the research problem statement. Students face challenges in articulating the research problem statement. Clearly articulating the research problems statement influences the success of the entire dissertation. Methodology: This paper uses a widely u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Doing the writing in one step can be challenging for a majority of the students. Instead, the suggestion by Ali and Pandya (2021) was to break down the process of writing a research problem statement into four stages. Each phase asks the student a series of questions, with the intent of activating the analytical process.…”
Section: The Four Stages Of Writing a Research Problem Statementmentioning
confidence: 99%
See 4 more Smart Citations
“…Doing the writing in one step can be challenging for a majority of the students. Instead, the suggestion by Ali and Pandya (2021) was to break down the process of writing a research problem statement into four stages. Each phase asks the student a series of questions, with the intent of activating the analytical process.…”
Section: The Four Stages Of Writing a Research Problem Statementmentioning
confidence: 99%
“…In this section, we present rubrics that we suggest including in doctoral courses that teach and prepare the students to write their research problem statement. We align these rubric steps along with the four stages to writing a research problem statement suggested by Ali and Pandya (2021). For each stage, we are going to list the objective of the stage, explain about the step and then provide a set of questions.…”
Section: Development Of Instructional Rubrics For the Research Proble...mentioning
confidence: 99%
See 3 more Smart Citations